2008
DOI: 10.1111/j.1368-423x.2008.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Representation theorem for convex nonparametric least squares

Abstract: We examine a nonparametric least squares regression model where the regression function is endogenously selected from the family of continuous, monotonic increasing and globally concave functions that can be nondifferentiable. We show that this family of functions is perfectly represented by a subset of continuous, piece-wise linear functions whose intercept and slope coefficients are constrained to satisfy the required monotonicity and concavity conditions. This representation theorem is useful at least in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
137
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 33 publications
2
137
0
4
Order By: Relevance
“…When all inequalities of (6) are satisfied, we can employ the Afriat's Theorem to show that there exist a continuous, monotonic increasing and concave functionĝ that satisfies y i ¼ĝðx i Þ þ t i for all i = 1,…,n. As Kuosmanen (2008) emphasizes, the Afriat inequalities are the key to modeling the concavity axiom in the general multiple regression setting where there is no unambiguous way of sorting input vectors x. For estimating the shape of the production function, the coefficients (a i ,b i ) have a compelling economic interpretation: vector b i can be interpreted as the subgradient vector rgðx i Þ, and thus it represents the vector of marginal products of inputs at point x i .…”
Section: Stage 1: Cnls Estimationmentioning
confidence: 99%
See 4 more Smart Citations
“…When all inequalities of (6) are satisfied, we can employ the Afriat's Theorem to show that there exist a continuous, monotonic increasing and concave functionĝ that satisfies y i ¼ĝðx i Þ þ t i for all i = 1,…,n. As Kuosmanen (2008) emphasizes, the Afriat inequalities are the key to modeling the concavity axiom in the general multiple regression setting where there is no unambiguous way of sorting input vectors x. For estimating the shape of the production function, the coefficients (a i ,b i ) have a compelling economic interpretation: vector b i can be interpreted as the subgradient vector rgðx i Þ, and thus it represents the vector of marginal products of inputs at point x i .…”
Section: Stage 1: Cnls Estimationmentioning
confidence: 99%
“…Since conventional DEA literature emphasizes the fundamental philosophical difference between DEA and the regression techniques (e.g., Cooper et al 2004), the intimate links between DEA and regression analysis may not have attracted sufficient attention. In this respect, the recent studies Kuosmanen (2008) and Kuosmanen and Johnson (2010) have shown that DEA can be understood as a constrained special case of nonparametric least squares subject to shape constraints. More specifically, Kuosmanen and Johnson (2010) prove formally that the classic outputoriented DEA estimator can be computed in the singleoutput case by solving the convex nonparametric least squares (CNLS) problem (Hildreth 1954;Hanson and Pledger 1976;Groeneboom et al 2001a,b;Kuosmanen 2008) subject to monotonicity and concavity constraints that characterize the frontier, and a sign constraint on the regression residuals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations